What are the indications for treatment of hypercholesterolemia with statin therapy in obese children?. Issue 6 (June 2017) - Rommen, Michael C; Howard, Carol
Abstract : EVIDENCE‐BASED ANSWER : After 6 months of dietary and lifestyle modifications, statin therapy should be considered for children 11 to 21 years old with a BMI ≥97th percentile and LDL‐C ≥160 mg/dL or if LDL‐C is between 130 and 160 mg/dL and other risk factors or conditions are present. For similar children with BMI between 95th and 97th percentile, statin therapy should be considered if LDL ≥130 mg/dL if other risk factors or conditions are present (SOR: C, meta‐analysis of RCTs with disease‐oriented outcomes and evidence‐based guideline).